2019
DOI: 10.30607/kvj.592883
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Trolox and Alpha-Lipoic Acid on Post-Thawed Pırlak Ram Sperm Parameters, Oxidative Stress and DNA Damage in Non-Breeding Season

Abstract: The present study was conducted to examine the protective roles of trolox and alpha-lipoic on post-thawed Pirlak ram sperm parameters, oxidative stress and DNA damage in non-breeding season. Semen samples from 5 healty Pırlak rams (2-3 years of age) were used in the study. Six ejaculates for each rams were collected and pooled. Ejaculates were split into three aliquots and diluted to a final concentration of 150x10 6 spermatozoa/ml with the base extender containing 1 mM alpha lipoic acid, 1 mM trolox and no ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Avdatek et al. (2019) reported that 1 mmol L −1 alpha‐lipoic acid better preserved the plasma membrane integrity compared to their control group. These differences might be caused by the techniques used in the dilution and freezing of semen, and the differences in the content of the diluent.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Avdatek et al. (2019) reported that 1 mmol L −1 alpha‐lipoic acid better preserved the plasma membrane integrity compared to their control group. These differences might be caused by the techniques used in the dilution and freezing of semen, and the differences in the content of the diluent.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings show that 0.25 mmol L −1 and 0.50 mmol L −1 alpha-lipoic acid supplementation increased the post-thaw plasma membrane functional integrity rate compared to the control group. Avdatek et al (2019) reported that 1 mmol L −1 alpha-lipoic acid better preserved the plasma membrane integrity compared to their control group. These differences might be caused by the techniques used in the dilution and freezing of semen, and the differences in the content of the diluent.…”
Section: Ta B L E 1 Mean Of Studied Sperm Resilience Parameters On Di...mentioning
confidence: 98%
See 3 more Smart Citations